2019
DOI: 10.3389/fmicb.2019.02615
|View full text |Cite
|
Sign up to set email alerts
|

Co-infection of Mycoplasma gallisepticum and Escherichia coli Triggers Inflammatory Injury Involving the IL-17 Signaling Pathway

Abstract: Mycoplasma gallisepticum and Escherichia coli are well known respiratory disease-inducing pathogens. Previous studies have reported that co-infection by MG and E.coli causes significant economic loss in the poultry industry. In order to assess the respiratory toxicity of co-infection in chicken lung, we established a co-infection model to investigate changes in the inflammatory cytokines, lung tissue structure, and transcriptome profiles of chicken lung. The results showed that co-infection caused a wider rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 49 publications
6
33
0
Order By: Relevance
“…The Co-infection group (B): 0.2 ml of MG medium (1 × 10 9 CCU/ml) was injected into the left caudal thoracic air sac at 7 th day, and 0.1 ml of E.coli bacteria (10 9 CFU/ml) was injected intraperitoneally at day 10 [ 25 ]. Four methods were used to verify whether the three models were successfully established including PCR tests, serological tests, pathological observations and pathogen isolation as previously described [ 21 , 26 ].…”
Section: Experimental Models Establishment and Groupingmentioning
confidence: 99%
See 2 more Smart Citations
“…The Co-infection group (B): 0.2 ml of MG medium (1 × 10 9 CCU/ml) was injected into the left caudal thoracic air sac at 7 th day, and 0.1 ml of E.coli bacteria (10 9 CFU/ml) was injected intraperitoneally at day 10 [ 25 ]. Four methods were used to verify whether the three models were successfully established including PCR tests, serological tests, pathological observations and pathogen isolation as previously described [ 21 , 26 ].…”
Section: Experimental Models Establishment and Groupingmentioning
confidence: 99%
“…14/31 metabolites in the co-infection-specific metabolic signature mapped onto their interconnecting pathways and the involved genes were also added to the map. The expression of related genes was screened from our previous RNA-seq results by the BGI data mining online website ( http://report.bgi.com ) as explained in previously [ 21 ]. The results showed that the expression of LTC4 S and ALOX5AP in co-infection was elevated significantly compared to control group, while the expression of CYP2C21 L and LTA4 H were decreased significantly, and the other genes showed no significant differences.…”
Section: Changes In Expression Of Arachidonic Acid Pathway-related Prmentioning
confidence: 99%
See 1 more Smart Citation
“…A piece of bursal sample was processed for histopathological examination as described previously (21). In brief, samples were fixed in 10% formalin for 12 h, dehydrated in a series of ethanol solution, embedded in wax and cut into tiny sections for mounting on glass slides.…”
Section: Histopathological and Ultrastructural Observationmentioning
confidence: 99%
“…We have selected six TCMs according to this method, while the optimal combination of Chinese medicine is still an obstacle to the development of Chinese medicinal compound (CMC). In this study, we focus on the strategy for optimizing the combination of active components of CMC based on our laboratory's model research [7] .…”
Section: Introductionmentioning
confidence: 99%